Impact of environmental drivers on ecosystem service-delivery of small garden trees in a temperate climate - Larsen, Elisabeth K.; Blanusa, Tijana; Tanner, Rachael; Barker, Joseph; Dunn, Nick; Gush, Mark B. (Frontiers in Environmental Science, 2025)
Green infrastructure has an increasingly important role in mitigating urban environmental concerns such as heat island effect, localised flooding, pollution and biodiversity loss. Trees are a crucial element of that, and in the UK, around 25% of the urban tree canopy consists of trees within domestic gardens, which provide valuable ecosystem services. With the average UK garden size being only 188 m2 and urban areas being under pressure from climate change, information on small garden trees, suitable for these spaces is increasingly important. To address this gap, we studied nine taxa of small-stature garden trees (representing a range of functional and structural tree characteristics) in a replicated outdoor experiment over two summers (2021 and 2022). In this paper, we focused on the sap flux patterns of selected taxa in response to measured environmental drivers (solar radiation, air temperature, relative humidity, wind speed and soil temperature), as well as trees’ above-ground size and biomass growth. Results showed that the strongest driver of sap flux across all taxa was a reduction in relative humidity, followed by an increase in radiation and a rise in air temperature. The results depended on time of day and the specific taxon. Overall, Malus ‘Scarlett’ had the highest sap flux density in the morning, while Crataegus ‘Prunifolia Splendens’ averaged the highest sap flux density during afternoon and evening. Both taxa would be suitable garden trees to provide soil moisture reduction and cooling in smaller gardens during the growing season. Taxa with compact canopies in combination with high water demand such as Cupressus, Ilex and Pyrus in this study, provided the most transpirational cooling relative to size. This demonstrates how “the bigger the better” is not necessarily the case for transpirational cooling. Rather, the ratio between sapwood- and crown volume in combination with water demand, might be a better indicator of transpirational cooling efficiency.